Analysis of Fire Risk Assessment in Piperack Area with Fishbone Method and Failure Mode and Effect Analysis (FMEA) at PT XYZ - Abdillah Ihza Ahyana, Rafly; Setyo Wibowo, Dewa; Dwi Pangestu, Bagas; Galuh Agatha, Orizalia; Sulistyo Nugroho, Budi (Advances In Social Humanities Research, 2024)
Fire risk is a work safety problem that often occurs in an industry. The pipe rack area at PT XYZ has a large potential fire risk due to the presence of flammable materials and sustainable production activities. The identification and analysis process regarding the causes of fire incidents is urgently needed to formulate preventive measures. By using the fishbone diagram analysis method, the root cause of potential fires can be identified and the Failure Mode and Effect Analysis (FMEA) method can be found out the value of the severity. The results of the study show that six basic causes affect the occurrence of fires. Through FMEA, several high-risk failure modes can be identified and prioritized as cracks in pipe joints in pipe fitting components. Recommendations for preventive measures include increasing occupational safety training, regular equipment maintenance, improving fire early detection systems, and implementing occupational safety standards.